The effect of training program toward hand hygiene compliance among registered nurses in a private hospital in Klang Valley - Kogilah Krishnan; Annamma Kunjukunju; Aini Ahmad; Puan Nurhanisah Chakari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hand hygiene is the most effective way to prevent hospital-acquired infections (HAI). Although the percentage of the HAI performance indicator target was still less than 5%, this study was carried out to reinforce hand hygiene compliance among registered nurses to increase the quality of nursing services. Purpose: To determine the effect of a training program on hand hygiene compliance among registered nurses in a private hospital. Method: This study used a quantitative quasi-experimental design based on an experimental group (single group) among 48 registered nurses from A&E, ICU, OT, PAED, LR, O&G, hemodialysis, and medical-surgical services working in KPJ Sentosa Hospital. The researcher used an audit monitoring pre and post-training to observe an opportunity to perform their hand hygiene practice, adapted from WHO as validated tools in this study. The 5-moment of hand hygiene before touching a patient, before clean/aseptic procedures, after body fluid exposure or risk, after touching a patient, and after touching the patient's surroundings, besides seven steps of hand hygiene compliance were included in this study determine the effect of training program's on hand hygiene compliance among registered nurses. Results: The mean percentage of hand hygiene compliance in the post-test (M = 6.85) after the intervention was significantly higher than before the intervention (M = 6.63). Additionally, the significant (2-tailed) value is 0.020. A p-value <.0.020 was considered statistically significant. Conclusion: Therefore, continuous training programs should continue to enhance the hand hygiene compliance rate among healthcare workers, and the impact will reduce hospital-acquired infections and establish the hospital’s image well in the community.